Durability of the adhesive cementation to the dentin substract - BRAZ,Rodivan (2016)
ABSTRACT Objective The aim of this study was to evaluate, in vitro, the union stability of resin cements to the dental substract through microtensile bond strength (µTBS) analysis and scanning electron microscopy (SEM). Methods Fifty-four third human molars, stored in water for a short (24 hours) and long period of time (1 year) presented a flat oclusal superficial dentin. The teeth were distributed in six different groups: G1- Panavia F2.0/Kuraray; G2- RelyXUnicem/3M ESPE; G3- G-Cem/GC; G4- Biscem/ Bisco; G5- Panavia F2.0/Kuraray without pre-treatment and G6- Multilink Sprint/Ivoclar-Vivadent which were adhered to its respective indirect resin composite restoration, (G1- Clearfil AP-X/Kuraray; G2- Filtek Z350/3M ESPE; G3- Gradia Direct X(tm)/GC; G4- Aelite(tm)/ Bisco; G5- Clearfil AP-X/Kuraray; G6- Tetric Ceram/ Ivoclar-Vivadent). The resin blocks were cemented and the sticks were obtained by tooth, with an area of adhesive interface of 0,8mm² (±0,2). Results The mean values, submitted to Mann-Whitney and Kruskal-Wallis tests (α = 5%) were in MPa after 24 hours: G1 = 9.66 (A), G2 = 13.37 (A); G3 = 15.89 (A); G5 = 4.18 (B); G6 = 11.01 (A) and after 1 year: G1 = 9.75 (A), G2 = 11.73 (A); G3 = 20.10 (B); G5 = 6.80 (A); G6 = 21.09 (B). All G4 group presented pretest failures. Conclusion During the one year period, with the exception of BisCem, the self-adhesive resin cements were a favorable alternative for the adhesive cementation, standing out among these, the G-Cem and Multilink Sprint.